Effects of Dietary Probiotic (Bacillus subtilis) Supplementation on Carcass Traits, Meat Quality, Amino Acid, and Fatty Acid Profile of Broiler Chickens - Tang, Xiaopeng; Liu, Xuguang; Liu, Hu (Frontiers in Veterinary Science, 2021)
The aim of the present study was to evaluate the effects of dietary supplementation with or without Bacillus subtilis (B. subtilis) on carcass traits, meat quality, amino acids and fatty acids of broiler chickens. In total, one hundred and sixty one-day-old Arbor Acres male broiler chicks were divided into 2 groups with 8 replicates of 10 chicks each. Chickens were received basal diets without (CN group) or with 500 mg/kg B. subtilis (BS group) for 42 days. Eight chickens from each group were slaughtered at the end of the trial, and carcass traits, meat quality, chemical composition, amino acid and fatty acid profile of meat were measured. The results showed that the breast muscle (%) was higher in BS than in CN (P < 0.05), while abdominal fat was decreased of that (P < 0.05). The pH24h of thigh muscle was increased (P < 0.05) when supplementary with BS; however, drip loss, cooking loss of breast muscle, and shear force of thigh muscle were decreased of that (P < 0.05). Lysine (Lys), methionine (Met), glutamic acid (Glu) and total essential amino acid (EAA) in breast muscle and Glu in thigh muscle were greater in BS than in CN (P < 0.05). C16:1, C18:1n9c and MUFA in breast muscle and thigh muscle were greater in BS than in CN (P < 0.05). In conclusion, dietary supplementation with B. subtilis could improve the carcass traits and meat quality of broilers, which is benefit for the consumers due to the improved fatty acid profile and amino acid composition.